Dynamic Architectural Reconfiguration Algorithms and Transmission Protocols for Clustered Sensor Network Topologies with Prioritized Data. (16th August 2012) - Salem, Fatma; Burrell, A. T.; Papantoni-Kazakos, P.
Abstract : The objective of a sensor network is the execution of specific signal processing functions on data that are collected in a distributed fashion. The transmission of the data is facilitated by protocols whose operations may be constrained by physical limitations of the network units, while their performance must simultaneously comply with the performance requirements of the deployed signal processing operations. At the same time, the network architecture affects the performance of both the signal processing and the data transmission operations, while some of the sensors may generate high-priority data. In this paper, we consider clustered sensor network topologies deploying a specific stable random access transmission algorithm per cluster, which facilitates high-priority data. We then introduce a dynamic architectural reconfiguration algorithm which controls individual cluster rates for optimal overall network performance. The latter algorithm is facilitated by a high-level traffic rate monitoring protocol.